SHARIA FINANCING IN THE AGRICULTURAL SECTOR: SOLUTIONS TO THE PROBLEM OF USURY FROM A SOCIAL AND ECONOMIC PERSPECTIVE - Larasati, Pradipta Puspita; Fitriyah, Sayyidatul; Widiastuti, Tika; Berkah, Dian (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2017)
As an agricultural country, the agricultural sector has a vital role in the development of the national economy. But it does not mean the agricultural sector work without an obstacle. In fact the sector is often faced with various problems, especially in the weakness of capital. The capital needs will increase along with various choices of commodities and cropping patterns, the development of cultivation technology, post- harvest handling and processing of increasingly rapid results. In the era of agricultural technology, intensive of capital mobilization for both agricultural equipment and production facilities. Farmers can not afford to finance their farms with their own funds so that the farmers decide to finance the majority of which come from conventional lending institutions or even loan sharks and "moneylenders” based on the interest system which contains the element of riba. This is what causes financing by using islamic financial institutions are still minimal. Over this condition, making an opportunity as well as a challenge for islamic financial institutions to be present in the community, especially farmers in the agricultural sector, in order to minimize the action of riba in economic activity. As a solution, sharia financial institutions offer appropriate financing schemes in accordance with the needs of farners, but it can also be through the optimization of the function of islamic microfinance institutions (BMT) as an alternative in financing in the agricultural sector, the establishment of agricultural sharia banking and the application of rewards and punishment in financing. So the purpose of this study is expected by closer farmers with islamic financial institutions so that they can be completely free from the riba that can harm.Keywords:Riba, Agricultural Development, Sharia Financing, Islamic Financial Institutions, Islamic Banking.